The Hidden Costs of Medical AI: Beyond the Balance Sheet - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The Hidden Costs of Medical AI: Beyond the Balance Sheet The integration of Artificial Intelligence (AI) into healthcare promises a revolution: faster d...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care